STRATEGIES FOR EFFECTIVE TEACHING OF BUSINESSEDUCATION IN TERTIARY INSTITUTIONS INANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study ascertained business educators’ rating of equipment maintenance strategies for effectiveteaching of business education in tertiary institutions in Anambra State. Two research questionsguided the study and four hypotheses were tested at 0.05 level of significance. The study adoptedthedescriptive research design. The population of the study comprised 122 business educators in the sixtertiary institutions in Anambra State. The instrument for data collection was a 22-itemquestionnairestructured on a 5-point rating scale of Very High Extent (VHE), High Extent (HE), Moderate Extent(ME), Low Extent (LE) and Very Low Extent (VLE). The instrument was validated by three expertsin business education in Nnamdi Azikiwe University, Awka. To determine the reliability of theinstrument, a pilot test was conduct. Test on reliability of the instrument using Cronbach Alphamethod which yielded the scores of 0.73, 0.76, for clusters B1 and B2 respectively. Descriptivestatistics of mean and standard deviation was used to answer the research questions and determine thehomogeneity or otherwise of the respondents’ views. The hypotheses were analyzed with one wayAnalysis of Variance and t-test. Findings revealed that business educators rated to a high extent thatpreventive and corrective measures were effective equipment maintenance strategies for effectiveteaching of business education in tertiary institutions in Anambra State. Findings also showedthatgender and institution type influenced the respondents’ opinion. Based on these findings, theresearchers recommended that administrators of business education programme in tertiary institutionsshould regularly organize training programme for business educators and technologist on preventivestrategies for maintaining equipment in the business education programme
Keywords: Equipment maintenance, strategies, teaching, Business Education.